The expression of modal verbs in translation of decision gender: contributions to foreign language teaching - Poletto Lugli, Viviane Cristina (Universidade Estadual Paulista, 2017)
This article aims to present the relationship between text genres and the manifestation of modal verbs in translated texts and itendorses the view of text genres essential for learning a foreign language. It is a bibliographic research that identifies the meaning of modal verbs in Portuguese, Spanish and English versions of the decision genre, published by the Official Journal of the European Union. It is based on the principle that text genres work as instruments (DOLZ; SCHNEUWLY, 2004) for interpretation and text prodution in translation that consistes in the retextualization (ARROJO, 2003), in the transformation (ARROJO, 1993) of the source text. In accordance with this perspective, this article considers the relevance of the study of textual genres, modal verbs and communicative situations in the teaching of foreign languages via translation, understading that learning a foreign language and translating doesn't only require linguistic skills.